Biological and Physical Factors in Population Distribution and Territorial Defence of Fiddler Crabs, Uca vocans hesperiae - BUNNUANG, Kanchana; MEESAWAD, Kumpul; JAROENSUTASINEE, Mullica; JAROENSUTASINEE, Krisanadej (Walailak Journal of Science and Technology (WJST), 2011)
The study investigated the physical and biological factors relating to population distribution and territorial defence of Uca vocans hesperiae habitat in Libong non-hunting area, Trang Province, southern Thailand. The area under study was divided into 3 zones: Zone 1, Zone 2, and Zone 3 that were 2, 4, and 6 m from the water edge respectively. Zone 1 contained higher levels of organic matter, moisture content, population density, male feeding rate, and more burrows than the other two zones. Zone 1 also had 1:1 adult sex ratio of male to female compared with the more female biased ratios for Zone 2 and Zone 3. Males had greater carapace width and length than females. Male territorial defenders had larger and longer carapaces, propodus, and dactylus than the average males in the population. The amount of organic matter did not have a direct bearing on the physical dimensions of territorial males in this species.